Identification of partially occluded map symbols - Korpi, Jari Arvi; Haybatollahi, Mohammad; Ahonen-Rainio, Paula (Cartographic Perspectives, 2014)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Times New Roman","serif"; mso-ansi-language:EN-US; mso-fareast-language:EN-US;} --> <!--[endif] --> Maps should be legible at all scales, and the information density of a map should be adapted to fulfill this goal. However, there are situations in which overlapping symbols might not be easily avoided. These kinds of cluttered or over-plotted situations often occur today in geovisual analytics and in map mash-ups created using Web 2.0 technologies. In this research project, we examine via a user test the extent to which occluded symbols can still be identifiable. Specifically, we tested how different levels of occlusion affected the accuracy and response time of finding symbols that varied in either color hue, abstract shape, or pictogram. The results of the test show that the efficiency of the symbols decreases when the symbols become partially occluded. Still, even half-occluded complex shapes can be identified quite accurately. Symbols varying in color hue seem to tolerate occlusion the best.